Development and Characterization of Emulsion Gels with Pine Nut Oil, Inulin, and Whey Proteins for Reduced-Fat Meat Products - Berik Idyryshev; Alibek Muratbayev; Marzhan Tashybayeva; Assem Spanova; Shyngys Amirkhanov; Assel Serikova; Zhaksylyk Serikov; Laila Bakirova; Madina Jumazhanova; Aigerim Bepeyeva (Foods)
An emulsion gel was developed to replace animal fats in meat products while preserving desirable sensory and structural attributes. The gel was prepared by emulsifying pine nut oil and sunflower oil with whey protein concentrate (WPC) and polysaccharides (inulin and carrageenan). Process parameters, including the inulin-to-water ratio, homogenization speed, and temperature, were optimized to achieve stable gels exhibiting high water- and fat-binding capacities. Scanning electron micrographs revealed a cohesive network containing uniformly dispersed lipid droplets, with carrageenan promoting a denser matrix. Chemical assessments demonstrated a notably lower saturated fatty acid content (10.85%) and only 0.179% trans-isomers, alongside an elevated proportion (71.17%) of polyunsaturated fatty acids. This fatty acid profile suggests potential cardiovascular health benefits compared with conventional animal fats. Texture analyses showed that carrageenan increased gel strength and hardness; Experiment 4 recorded values of 15.87 N and 279.62 N, respectively. Incorporation of WPC at moderate levels (3–4%) further enhanced the yield stress, reflecting a robust protein–polysaccharide network. These findings indicate that the developed emulsion gel offers a viable alternative to animal fats in meat products, combining superior nutritional attributes with acceptable textural properties. The substantial polyunsaturated fatty acid content and minimal trans-isomers, coupled with the gel’s mechanical stability, support the feasibility of creating reduced-fat, functional formulations that align with consumer demands for healthier alternatives.